A case of acute myocardial infarction due to Kounis syndrome after brachytherapy for prostate cancer - Mori, Shoji; Fukagai, Takashi; Oshinomi, Kazuhiko; Nagata, Masakazu; Morita, Masashi; Kato, Masako; Morota, Madoka; Ito, Yoshinori; Furuya, Takahiro (Journal of Contemporary Brachytherapy, 2025)
Major systemic complications during and immediately after brachytherapy are rare. Herein, we described a case of acute myocardial infarction due to Kounis syndrome after low-dose-rate brachytherapy in a 70-year-old man with a banana allergy. Following low-dose-rate brachytherapy under general anesthesia, the patient complained of itching throughout his body; electrocardiography showed ventricular fibrillation. Cardiac catheterization revealed 99% stenosis in the left anterior descending artery; consequently, percutaneous coronary intervention was performed promptly. In this case, Kounis syndrome was considered, which was caused by latex allergy to condoms used during trans-rectal ultrasound examinations.